(3fRgI GdNGWQ hHSJGf GdfGXQs ((3Ydj Hf MLGRj Hf MjOQ GdSHcj GdTGaYj GdCRgQj s)
(3ChdgG (B:s
(3GdHGH GdChd ef GdcKjQ hLOkG hThbkG, Edi CMSf GdfGS oNdbkG hnNdbkG ef GdhMjO GdaQjO Edi GdgdGd GdLOjO s
(3BNQgG (B:s
(3ef GdHGH GdYGTQ Je cJGH fRgI GdNGWQ hHSJGf GdfGXQ Ydi GdceGd hGdJeGe hfYhP HGddg ef GdRjGOI hGdfbUGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3jMJhj Ydi YTQI CHhGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs